Hearing Instruments for Unilateral Severe-to-Profound Sensorineural Hearing Loss in Adults: A Systematic Review and Meta-Analysis. Issue 5 (September 2016) - Kitterick, Pádraig Thomas; Smith, Sandra Nelson; Lucas, Laura
Abstract : Objectives: A systematic review of the literature and meta-analysis was conducted to assess the nature and quality of the evidence for the use of hearing instruments in adults with a unilateral severe to profound sensorineural hearing loss. Design: The PubMed, EMBASE, MEDLINE, Cochrane, CINAHL, and DARE databases were searched with no restrictions on language. The search included articles from the start of each database until February 11, 2015. Studies were included that (a) assessed the impact of any form of hearing instrument, including devices that reroute signals between the ears or restore aspects of hearing to a deaf ear, in adults with a sensorineural severe to profound loss in one ear and normal or near-normal hearing in the other ear; (b) compared different devices or compared a device with placebo or the unaided condition; (c) measured outcomes in terms of speech perception, spatial listening, or quality of life; (d) were prospective controlled or observational studies. Studies that met prospectively defined criteria were subjected to random effects meta-analyses. Results: Twenty-seven studies reported in 30 articles were included. The evidence was graded as low-to-moderate quality having been obtained primarily from observational before-after comparisons. The meta-analysis identified statistically significant benefits to speech perception in noise for devices that rerouted the speech signals of interest from the worse ear to the better ear using either air or bone conduction (mean benefit, 2.5 dB). However, these devices also degraded speech understanding significantly and to a similar extent (mean deficit, 3.1 dB) when noise was rerouted to the better ear. Data on the effects of cochlear implantation on speech perception could not be pooled as the prospectively defined criteria for meta-analysis were not met. Inconsistency in the assessment of outcomes relating to sound localization also precluded the synthesis of evidence across studies. Evidence for the relative efficacy of different devices was sparse but a statistically significant advantage was observed for rerouting speech signals using abutment-mounted bone conduction devices when compared with outcomes after preoperative trials of air conduction devices when speech and noise were colocated (mean benefit, 1.5 dB). Patients reported significant improvements in hearing-related quality of life with both rerouting devices and following cochlear implantation. Only two studies measured health-related quality of life and findings were inconclusive. Conclusions: Devices that reroute sounds from an ear with a severe to profound hearing loss to an ear with minimal hearing loss may improve speech perception in noise when signals of interest are located toward the impaired ear. However, the same device may also degrade speech perception as all signals are rerouted indiscriminately, including noise. Although the restoration of functional hearing in both ears through cochlear implantation could be expected to provide benefits to speech perception, the inability to synthesize evidence across existing studies means that such a conclusion cannot yet be made. For the same reason, it remains unclear whether cochlear implantation can improve the ability to localize sounds despite restoring bilateral input. Prospective controlled studies that measure outcomes consistently and control for selection and observation biases are required to improve the quality of the evidence for the provision of hearing instruments to patients with unilateral deafness and to support any future recommendations for the clinical management of these patients. Abstract : Adults with a unilateral severe-to-profound sensorineural hearing loss report difficulties with listening in many everyday situations. Current hearing instruments attempt to alleviate these difficulties either by rerouting sounds from the impaired ear to the non-impaired ear or by restoring hearing in the impaired ear. A systematic review and meta-analysis evaluated the evidence for their use. The evidence was of low-to-moderate quality. Meta-analyses found benefits to speech perception in noise and reductions in listening difficulty. Controlled trials are needed to provide higher-quality evidence for hearing instrument use in unilateral deafness and to support recommendations for the clinical management of these patients.Supplemental Digital Content is available in the text.